2002
DOI: 10.1055/s-2002-33335
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity in the Chemistry of Oxygen-Centered Radicals - The Formation of Carbon-Oxygen Bonds

Abstract: In recent years, powerful new methods for the generation of alkoxyl radicals under mild and neutral conditions have been developed. This progress has led to a thorough investigation of most O-radical elementary reactions. Today, sufficiently reliable thermodynamic and kinetic data are available either from experimental or from theoretical studies in order to predict alkoxyl radical reactivities and selectivities in synthesis. For instance, alkoxyl radicals readily add to carbon-carbon and carbon-nitrogen doubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
104
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 180 publications
(104 citation statements)
references
References 103 publications
(173 reference statements)
0
104
0
Order By: Relevance
“…This knowledge has been applied in the present study in order to develop a halocyclization of alkenols, which profits from mild reaction conditions and synthetically useful radical selectivities. [16] The choice of aryl-substituted bis(homoallylic) alcohols 1 for this purpose has been governed by their UV activity, which also facilitated spotting of bromo-or iodocyclization products 4 or 5 even in minor concentrations on TLC plates in the course of the purification step (column chromatography). The major task of the present contribution has been associated with finding matching combinations of: (i) a suitable method for initiating bromo-or iodocyclizations in a radical chain reaction, (ii) an adequate trapping reagent for halogen atom delivery onto a cyclized radical 3, and (iii) an appropriate chaincarrying radical X· that preferentially regenerates alkoxyl radical 2 in a succeeding step before competing side reactions consume either the alkoxyl radical precursor, for example 6a, or any essential intermediate of the cycle that is outlined in Figure 4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This knowledge has been applied in the present study in order to develop a halocyclization of alkenols, which profits from mild reaction conditions and synthetically useful radical selectivities. [16] The choice of aryl-substituted bis(homoallylic) alcohols 1 for this purpose has been governed by their UV activity, which also facilitated spotting of bromo-or iodocyclization products 4 or 5 even in minor concentrations on TLC plates in the course of the purification step (column chromatography). The major task of the present contribution has been associated with finding matching combinations of: (i) a suitable method for initiating bromo-or iodocyclizations in a radical chain reaction, (ii) an adequate trapping reagent for halogen atom delivery onto a cyclized radical 3, and (iii) an appropriate chaincarrying radical X· that preferentially regenerates alkoxyl radical 2 in a succeeding step before competing side reactions consume either the alkoxyl radical precursor, for example 6a, or any essential intermediate of the cycle that is outlined in Figure 4.…”
Section: Discussionmentioning
confidence: 99%
“…[15] Since intermediates 2 exhibit electrophilic properties, this strategy corre-sponds to an Umpolung of the polar bromocyclization and is therefore expected to provide selectivities (ring size, relative configuration, functional group compatibility), which are, in principle, not attainable in ionic transformations. [16,17] In view of these perspectives, we have performed a mechanistic study on the radical version of the halocyclization by addressing three major issues: (i) Nalkoxy-substituted thiazole-2(3H)-thiones 6 and pyridine-2(1H)-thiones 7, [18Ϫ21] in combination with a larger set of reactive halogen atom donors, were assessed in regard of their utility to serve as reagents for the synthesis of halocyclization products 4 and 5; (ii) a stereochemical analysis of alkoxyl radical cyclization products was accomplished by combining results from NMR and X-ray diffraction experiments; (iii) selectivities from the radical version of the bromocyclization were compared to those from NBS-mediated transformations, in order to characterize fields of application for both methods. Step 1: generation of alkoxyl radicals 2; step 2: stereoand regioselective ring-closure reaction; step 3: halogen atom trapping; R 1 ϪR 3 ϭ aryl or H; R ϭ H or CH 3 Table 1) [22,23] and suitable alkylating reagents.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, intramolecular processes (radical cyclizations), which generally proceed with excellent stereoselectivities, are widely used for the synthesis of oxygen-containing heterocycles. [2,3] In contrast to this, intermolecular addition reactions of O-centered radicals to CϵC triple bonds have as yet received considerably less attention.…”
Section: Introductionmentioning
confidence: 99%
“…• species under investigation [X • ϭ NO 2 • , [9Ϫ11] SO 3 •Ϫ , [12] H • , [13] RC • (O) [14] ] have never been found to react with the alkyne in a chain-propagation step. We have shown that the termination of this cyclization cas-cade is kinetically controlled and determined by the ease of the final homolytic cleavage of the OϪX bond.…”
Section: Introductionmentioning
confidence: 99%
“…CONCLUDING REMARKS Structure determines reactivity. Reactivity in turn is the basis for the diverse chemistry of acyclic organic peroxides 207,208 . Today, structure and bonding of peroxides are well understood.…”
Section: Acetogeninsmentioning
confidence: 99%